Atypical Laryngeal Infections: Localized Lesions from Unusual Organisms May Simulate Malignancy. (January 2020) - Yan, Kenneth; Taxy, Jerome B.; Paintal, Ajit; Friedman, Aaron D.
Objective: The identification of rare sources of laryngeal infection in immunocompetent patients. Recovered organisms were Mycobacterium tuberculosis (laryngeal tuberculosis [LTB]), Mycobacterium fortuitum (laryngeal Mycobacterium fortuitum [LMF]), and Blastomyces dermatiditis (laryngeal blastomycosis [LB]). Method: Single institution retrospective case series of three patients over a 2.5-year period and review of the literature on laryngeal infections by three atypical organisms. Results: Three patients presented with hoarseness and cough; one additionally had throat pain (LTB). Indirect laryngoscopy demonstrated diffuse laryngeal ulceration (LTB, LMF) and an exophytic, contiguous glottic mass (LB). Direct microlaryngoscopic biopsies and cultures established the diagnoses, including a frozen section in one case (LB), which prevented a simultaneously planned surgical resection. Appropriate antimicrobial therapy yielded dramatic laryngeal and corresponding vocal improvement, for which we provide unique photo and audio documentation. In the last 10 years, fewer than 500 cases of LTB have been reported in the English language medical literature, principally outside the United States. To date, there have been reports of only 34 LB and no cases of LMF. Conclusion: Atypical infections of the larynx may be localized and mimic laryngeal cancer on endoscopy. Tissue examination as well as microbiologic samples are diagnostic and complementary.